Knowlegde of medical students about oncology: Study with interns (Research, Society and Development, 2021)
The aim was to assess the knowledge of medical students about early detection, pain and palliative care management in oncology. A cross-sectional, descriptive with a quantitative approach study was adopted. A hundred and one medical interns of the medicine course of Centro Universitário de Patos, Paraíba. To collect data, between february and april of 2021, it was used an adapted questionnaire, available virtually through Google Forms. The data were analyzed on the Statistical Package of the Social Sciences (SPSS), 25 version. descriptive statistics were used on the demographics variables and central tendency measures. The answers involved a Likert-type scale, ranging from 0 (strongly disagree) to 4 (strongly agree). To make the comparison of means of knowledge and reliability in oncology, it was used the Shapiro-Wilk normality test and the Mann-Whitney test to compare the means between the 5th and 6th year groups of interns. The statistical significance adopted was 5%. Lastly, it was recognized that, although academics have an acceptable level of knowledge, it is necessary to improve the opportunity to offer this knowledge, given the importance and epidemiological prevalence of this disease. Therefore, there is a clear need for a greater focus on this theme in academic training and in the scientific production of these future physicians.